Role of blood and blood components transfusion in obstetric emergencies - Vaid, Parul; Kapoor, Bhavuk; Kapoor, Mayank; Kapoor, Bharat B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Common obstetric emergencies require blood and blood components transfusion. The use of blood and its components has become a lifesaving strategy in management of obstetric haemorrhage. This study was aimed to know the prevalence, indications and adverse reactions of blood and its components transfusion. Methods: A review of 405 patients of obstetric emergencies requiring blood and its component transfusion was done. Results: Prevalence of blood and blood components transfusion in obstetric emergencies in one-year period was 18.4%. Mostly women who received blood transfusions were multiparous (50.12%) and belonged to rural areas (62%). Anemia is a risk factor for obstetric emergencies and the mean pre transfusion hemoglobin ±SD was 8.04±1.38 (g/dl). Obstetric hemorrhage (68.6%) was the most common indication for transfusion and packed red cells were most commonly (54.07%) transfused. The overall percentage of adverse reactions seen during transfusion was 1.95%. Conclusions: The present study reinforces the importance of appropriate use of blood and its components in obstetric emergencies. Appropriate use of blood components avoids many of the hazards associated with use of whole blood. All blood components should be made available at peripheral hospitals as most of the patients require specific blood component and they are referred to tertiary care centre in emergencies which can be avoided.